PHILOSOPHYO FISLAMIC MARRIAGE: MULTI DISCIPLINARY ISLAMIC STUDIES - Nasution, Khoiruddin (Universitas Islam Negeri Mataram, 2017)
Abstract: This article aims to analyse the Philosophy of Islamic Marriage. This paper begins with the preliminary discussion on the issue followed by the delineation of philosophy of Islamic law drawing on textual discourses in the area. Conclusion of this paper are: Firstly, the philosophy of Islamic marriage is the purpose, the goal of Islamic marriage. Secondly, the objective, the purpose, and the goal of Islamic marriage are the same as and in line with the fulfillment of human needs. The fulfillment of this requirement accords with the motivation of marriage in psychology and family roles in Sociology. Therefore, the objective, the purpose, the goal of Islamic marriage as a philosophyofIslamicmarriagegohandinhandwithhumanneeds,psychology and Sociology. Thirdly, by synchronizing the Islamic law and objectives as well as the principles of Islamic marriage law may yield the philosophy of Islamic marriagelaw.